Governmentality and Translation: Re-thinking the Cultural Politics of Lineage Landscapes in Contemporary Rural China. (21st September 2021) - Chen, Ningning
Abstract: This paper explores the cultural politics of lineage landscapes in contemporary rural China. Drawing on a combined governmentality/translation approach and ethnographic fieldwork in rural Wenzhou, it examines how the state governs the production of lineage landscapes and how local lineages translate governmental technologies in complex ways. Empirical evidence reveals that the government develops diversified rationalities and modes of governance to direct the (re)construction of lineage landscapes. It is also found that local lineages are skilled at appropriating state discourses and practices as well as enrolling other (non-)human actors, thereby legitimizing their landscape projects of ancestral tombs and memorials. On the ground, they often displace state objectives with the production of their preferred landscape (for example, "chair" tombs). Respectful of ancestors, state agents sometimes turn a blind eye to local displacement; however, while encountering challenges from the higher-level government, they intensify regulation, but lineages still retain the capacity to negotiate with them. With sensitivity to the entanglement of diversified actors and their dynamic interactions, this paper underlines the multiplicity and contingency of state governance and societal responses. It also foregrounds the cultural politics of lineage landscapes as a process of translating governmental technologies characterized by continuous mobilization, displacement and negotiation in a heterogeneous network.